Odpowiedzi

2009-12-05T18:02:47+01:00
A) 7x²-4x-6x²+4-x²+5x= najpierw nalezy zredukowac x² = x+4
b)-2(3a-2b)-4a(2-3a+2b)= -6a+4b-8a+12a²-8ab=12a²-14a-8ab=a(12a-14-8b)
c) (4-x)(2x+5)-4 = 8x+20-2x²-5x-4=-2x²+3x+16
d) (4-2x)(3x-3)-2x(3x+1) = 12x-12-6x²+6x-6x²-2x=-12x²+16x-12


pozdrawiam:)
2009-12-05T18:03:49+01:00
A) 7x²-4x-6x²+4-x²+5x
b)-2(3a-2b)-4a(2-3a+2b)
c) (4-x)(2x+5)-4
d) (4-2x)(3x-3)-2x(3x+1)

a). -x+4
b). -2(3a-2b)-9a+12a²-8ab
-6a+4b-9a+12a²-8ab
-15a+4b+12a²-8ab
c). 8x+20-2x²-5x-4
3x+16-2x²
d).12x-12-6x²+6x-6x²-2x
16x-12-12x²